Investigation on Characterizing Heated Pulsating Flows with Hot Wire Anemometers - A Hands-On Approach - Marius Alexandru PANAIT (INCAS Bulletin, 2014)
The pulsating heated flows are traditionally a difficult subject to treat with conventional hot wire or film methods. Special factors that complicate matters are flow reversal and non linear flow effects of vortices and wire probe wake disturbances on the heat transfer to the hot film or wire sensor in heated pulsating flows. The presence of these strongly nonlinear and unknown terms leads to great difficulties in calibration of hot film probes in this particular regime. The paper analyses the current state of matters in the field and reports a series of solutions that have been practically tested in a case of a high speed pulsated heated flow. Normally such measurements are made in a non-contact fashion using a LDV system or various visualization techniques but there have been recent attempts to use a constant temperature hot wire anemometer system (CTA).To obtain meaningful calibration for hot wire films in hot pulsating flows, a comparison system on other principles (LDV) was used, as well as a specially designed nozzle to replace the calibrator unit that could not be operated with heated fluid due to structural integrity reasons. The method as described below works well for the expected speed range that could be generated using the special nozzle.